Performance appraisal in Western and local banks in China: the influence of firm ownership on the perceived importance of guanxi - Gu, Fan; Nolan, Jane (Taylor and Francis, 2015)
The Chinese cultural factor guanxi (personal relationships) has an important influence on the implementation and effectiveness of HRM practices in China. However, few studies have investigated how guanxi influences performance appraisal in organisations with different ownership structures. We investigated this issue by studying three banks operating in mainland China: a state-owned bank, a foreign-owned bank and a city commercial bank. Both quantitative (survey of 308 employees) and qualitative data (22 in-depth interviews) were used. Macro-level convergence and micro-level divergence were found among the banks. The reform of the performance appraisal system in the state-owned bank indicated a degree of convergence towards a form commonly found in Western banks, at least on the surface. However, there were differences at the implementation level in the three banks. The perceived influence of guanxi on performance appraisal was strongest in the state-owned bank and weakest in the foreign-owned bank. The reasons for this included generational differences in cultural values, the international experience of employees and managers, and the degree of alignment between senior managers and others over the purpose of appraisal. The study demonstrates the mutability of cultural characteristics in different organisational settings.